The different aspects of Islamic culture / Volume 3, The spread of Islam throughout the world - El Hareir, Idris, 1945-; Mbaye, Ravane (Paris, France : UNESCO Publishing, 2011)
"Islamic culture, which is still vigorous in spite of its great antiquity, set out to develop side by side a vision of the individual and of the universe, a philosophy and an art of living that can be seen in the impressive remains of its heritage that is an essential part of the whole of humankind's. Halted for a time by adverse historical conditions, this culture none the less found the strength within itself to re-emerge. Its fidelity to its roots does not prevent it from keeping up with the times and participating in contemporary forums and the stirring dialogue of cultures. This series of volumes on the manifold facets of Islamic culture is intended to acquaint a very wide public with such matters as: the theological bases of the faith and principles that constitute the bedrock of the overall structure; the status of the individual and of society in the Islamic world; the expansion of Islam since the Revelation: the Arab, Asian, African and European spheres espousing the new faith and the way in which the rights of converted peoples have been upheld; the vital contribution of Islamic civilization to the adventure of human knowledge in science and technology; the educational and cultural manifestations of Islamic civilization in literature, the visual arts and architecture; finally, Islam today between loyalty to its past and the inescapable conquest of modernity."--Publisher's website.
Introduction / Idris El Hareir -- I. The advent of the prophet and the Islamization of Arabia. The Prophet Muhammad and the universal message of Islam / Bahjat Kamil Abd al-Latif ; The emergence of the umma / Hashim Yahya al-Mallah ; The Islamization of the Arabian peninsula / Bahjat Kamil Abd al-Latif ; The historical process of the spread of Islam / Abd al Wahid Dhanun Taha -- II. The first stage in the spread of Islam. Jihād in Islam / Abd al-Salam Muhammad al-Sherif al-Alim ; Islam in Syria (ash-Shām) / Mohammad Nabih Aqil ; Islam in Bilād ar-Rāfidayn (Iraq) / Abd al-Amir Hussain Amin ; Islam in Egypt, Nubia and the Sudan / Ahmad Shalaby ; The Islamization of Africa / El Hadji Ravane M'Baye -- III. Universal dimensions of the spread of Islam. The ʻAbbāsid caliphate and the age of the sultanates / Clifford Edmund Bosworth ; Islam in the Maghrib (21-641/1041-1631) / Idris El Hareir ; Islam in al-Andalus and the Mediterranean Islands (91-898/710-1492) / Idris El Hareir ; Islam in Iran / Sadegh Aenehvand ; Islam in Asia Minor / Ahmet Yaçar Oçak ; Islam in Afghanistan / Abdallah Salem al-Zelitny ; Islam on the Indian subcontinent / Sayyid Rizwan Ali Nadwi -- IV. The spread of Islam throughout the world. The Crusades in the period AD 1096-1291 / Işin Demirkent ; The Crusades in the period AD 1291-1571 / Aliyya el-Ganzoury ; Islam in South-East Asia / Yusof Ahmad Talib ; Islam in Central Asia up to the Mongol invasion / Richard Frye ; Islam in Central Asia / Devin DeWeese ; Islam in the Balkans / Enes Karić ; Islam in the Far East / Hee-Soo Lee -- V. New horizons for the spread of Islam. Islam in Eastern and South-East Europe / Smail Balic ; Islam in North, Central, and South America / Muhammad Akbar ; Islam in Australia, New Zealand and the neighbouring islands / Taj al-Din al-Hilaly -- VI. Islam on the threshold of the modern world. Colonialism and Islam in sub-Saharan Africa / Iba Der Thiam ; Nation states and the unity of Islam / Iba Der Thiam.
Includes bibliographical references (pages 887-916) and index.
ENH
Trim Education
Keywords: Islam -- History; World history; Islam -- Social aspects; Islam; English language; Islam -- Social aspects; World history; History